1999
DOI: 10.2514/2.4415
|View full text |Cite
|
Sign up to set email alerts
|

Spacecraft Vibration Reduction Using Pulse-Width Pulse-Frequency Modulated Input Shaper

Abstract: Minimizing vibrations of a exible spacecraft actuated by on-off thrusters is a challenging task. This paper presents the rst study of pulse-width pulse-frequency modulated thruster control using command input shaping. Input shaping is a technique that uses a shaped command to ensure zero residual vibration of a exible structure. Pulse-width pulse-frequency modulation is a control method that provides pseudolinear operation for an on-off thruster. The proposed method takes full advantage of the pseudolinear pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
56
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 101 publications
(56 citation statements)
references
References 10 publications
0
56
0
Order By: Relevance
“…Due to nonlinear nature of the modulator, analytic methods such as describing function cannot produce accurately prediction over a large operation range. Instead, extensive numerical simulations have been carried out to study the e ects of these parameters on the performances of the modulator and the FSS [7,13] prior to this research. This paper only presents results from the numerical studies and details on PWPF parameter selection can be found in [13].…”
Section: Selection Of Pwpf Modulator Parametersmentioning
confidence: 99%
“…Due to nonlinear nature of the modulator, analytic methods such as describing function cannot produce accurately prediction over a large operation range. Instead, extensive numerical simulations have been carried out to study the e ects of these parameters on the performances of the modulator and the FSS [7,13] prior to this research. This paper only presents results from the numerical studies and details on PWPF parameter selection can be found in [13].…”
Section: Selection Of Pwpf Modulator Parametersmentioning
confidence: 99%
“…In general, pulse modulators produce a pulse command sequence to thruster valves by adjusting pulse width and/or pulse frequency [5]. So far different Pulse modulators such as pseudo-rate modulator [6], integral-pulse frequency modulator [7,8] and Pulse-Width Pulse-Frequency (PWPF) modulator [9,10,11,12] have been proposed and examined. In comparison with others, the PWPF modulator has several superior advantages such as close to linear operation, high accuracy and adjustable pulse width and pulse frequency [5].…”
Section: Introductionmentioning
confidence: 99%
“…Banerjee and Singhose 4,5) proposed application of input shaping for minimum-time control of a twolink flexible manipulator. Song et al 6) treated application of input shaping for reduction of vibration of a flexible spacecraft, using pulse-width pulse-frequency modulated thrusters. References 7 to 9 repeated experimental testing of command shaping techniques on flexible link manipulators.…”
Section: Introductionmentioning
confidence: 99%